Peningkatan Pengetahuan tentang Deteksi Dini Anemia pada Remaja Putri - Ariyanto, Ariyanto; Fatmawati, Tina Yuli; Efni, Nel (Jurnal Abdimas Kesehatan (JAK), 2025)
Anemia is a public health problem in Indonesia that can be experienced by all age groups from toddlers to old age. In Indonesia, around 12% of boys and 23% of girls suffer from iron deficiency anemia. Adolescent girls (rheumataries) are prone to suffering from anemia because they lose a lot of blood during menstruation. Adolescent girls who suffer from anemia may later be at risk of developing anemia during pregnancy. The aim of this community service is to increase the knowledge of young women in recognizing, understanding and early detection of anemia. The target is 30 female students of SMP N Jambi. Community service methods include lectures, discussions, mentoring. The results of the service showed that students' knowledge increased after being given health education about early detection of anemia by 90%. Recommended for young women to increase their understanding of anemia by participating in counseling organized by health workers and broadening their horizons through print and electronic media